Tapal Batas Krisis Lingkungan Hidup Perspektif Materialisme Baru - Rangga Kala Mahaswa (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
New materialism initiates a reexamination of the body, agency, nature, objects, and everything materiality. Also, this article attempts to illustrate a general view of the environmental crisis based on the new materialism approach. The environmental crisis is very limited in the view of the metaphysical investigation. At the same time, so the proposal of a new materialism agency-structure configuration provides a broad understanding of the environmental crisis. The materiality of the world is not passively comprehended but instead lives and sustains itself, including the crisis itself. Its implication of shifting subject s decentralization goes beyond the limitation of the definition of subject and object, and goes further for the possibility of a new understanding of ecological crisis. Since this introspection and self-adaptation of multiple political decisions in an irreducibly pluriversal a world of many worlds are considered the actual, authentic, and with unblocking constraints touch the relation between human and non-human in the materiality of the more-than-human world.